CD8 Epitope Escape and Reversion in Acute HCV Infection - Timm, Joerg (The Rockefeller University Press, 2004)
In the setting of acute hepatitis C virus (HCV) infection, robust HCV-specific CD8(+) cytotoxic T lymphocyte (CTL) responses are associated with initial control of viremia. Despite these responses, 70–80% of individuals develop persistent infection. Although viral escape from CD8 responses has been illustrated in the chimpanzee model of HCV infection, the effect of CD8 selection pressure on viral evolution and containment in acute HCV infection in humans remains unclear. Here, we examined viral evolution in an immunodominant human histocompatibility leukocyte antigen (HLA)-B8–restricted NS3 epitope in subjects with acute HCV infection. Development of mutations within the epitope coincided with loss of strong ex vivo tetramer and interferon γ enzyme-linked immunospot responses, and endogenous expression of variant NS3 sequences suggested that the selected mutations altered processing and presentation of the variant epitope. Analysis of NS3 sequences from 30 additional chronic HCV-infected subjects revealed a strong association between sequence variation within this region and expression of HLA-B8, supporting reproducible allele-specific selection pressures at the population level. Interestingly, transmission of an HLA-B8–associated escape mutation to an HLA-B8 negative subject resulted in rapid reversion of the mutation. Together, these data indicate that viral escape from CD8(+) T cell responses occurs during human HCV infection and that acute immune selection pressure is of sufficient magnitude to influence HCV evolution.